PENERAPAN PEMBELAJARAN CALISTUNG PADA ANAK-ANAK DI DUSUN XII DESA KLAMBIR LIMA KEBUN - Ayu, Ayu Iga Ardini (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2022)
Lack of communication between children and parents causes their children to have no desire for children to study with their parents. The importance of reading and knowing letters and numbers for children causes many parents to encourage their children to learn without paying attention to what kind of learning process their children want. . Therefore, in this study, we will apply calistung learning to children with learning that interests them. The method used in this study is a qualitative research method with data collection techniques used are interviews and early development and late development. From the results of this study, the calistung learning method taught to children in Hamlet XII Pasar II, Klambir Lima Kebun Village is quite effective, as evidenced by the positive responses of their parents. Given the importance of calistung, the learning process should not always be left to the teachers at school alone. The role of parents at home is needed for the success of the baby in the learning process. Parents can print their children according to their dreams and become pride for themselves and their nation.